Retrograde embolization of anterior tibial artery for an iatrogenic arterio-venous fistula causing left lower extremity claudication. Issue 8 (27th August 2018) - Qaja, Erion; Segal, Michael; Engler, Christopher; Badhey, Mohan; Sivakumar, Mahalingam
Abstract: Lower extremity angiogram is generally a safe and effective procedure with a low rate of vascular complications. We report here a unique case of a 33-year-old female with anterior tibial artery (ATA) to anterior tibial vein fistula formation after lower extremity endovascular intervention. This was initially treated with open repair of the fistula and ligation of ATA. However, patient continued to complain of claudication like symptoms. Patient subsequently had an endovascular embolization of ATA in a retrograde fashion. Recovery was unremarkable; patient was discharged home same day. Three months postoperatively patient denies leg pain, a follow-up arterial duplex failed to show presence of arterio-venous fistula. This case illustrates the effectiveness of an endovascular approach as a minimally invasive treatment for this uncommon complication that occurs after lower extremity endovascular intervention.